2016
DOI: 10.3109/17518423.2016.1150360
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and evaluation of procedures for the induction of speech among persons with developmental disabilities

Abstract: Results indicate that a number of procedures can induce speech among individuals with developmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…These barriers may impede later social, academic, and vocational success (Rao, Beidel, & Murray, 2008). Furthermore, deficits in communication are often associated with the development of challenging behavior and can have an impact on an individual's quality of life (Mulhern et al, 2016). Given the various challenges associated with failure to learn communication repertoires, and the empirical evidence that early intervention can ameliorate later challenges (Dunlap et al, 2006), empirical investigations of interventions to establish vocal verbal repertoires in children with ASD are extremely important.…”
mentioning
confidence: 99%
“…These barriers may impede later social, academic, and vocational success (Rao, Beidel, & Murray, 2008). Furthermore, deficits in communication are often associated with the development of challenging behavior and can have an impact on an individual's quality of life (Mulhern et al, 2016). Given the various challenges associated with failure to learn communication repertoires, and the empirical evidence that early intervention can ameliorate later challenges (Dunlap et al, 2006), empirical investigations of interventions to establish vocal verbal repertoires in children with ASD are extremely important.…”
mentioning
confidence: 99%
“…Historically, most of the published work establishing an evidence base for SLT communication intervention in ID has focused on children (Adams et al 2012;Pennington et al 2005;Mulhern et al 2017). Snell et al's (2010) systematic review, which found evidence supporting SLT intervention for individuals with severe disabilities, notes that the evidence is based on the paediatric population, with 80% of the published studies focusing on participants younger than 12 years.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of language interventions in autism incorporating Single Case Experimental Design evidence have either been unable to generate an effect size at all ( Lane et al, 2016 ; Mulhern et al, 2017 ), or have used the Percentage of Non-overlap statistic ( Kane et al, 2010 ), which is unfortunately limited due to ceiling effects ( Parker et al, 2011 ) and is confounded with length of baseline period ( Allison and Gorman, 1993 ). Furthermore, Lane et al (2016) assessed naturalistic spoken language interventions in autism for methodological quality and found that only half the Single Case Experimental Design studies (24 studies, n = 45) were of adequate quality.…”
Section: Introductionmentioning
confidence: 99%